Colour Doppler ultrasonography evaluation of vascularization in the wrist and finger joints in rheumatoid arthritis patients and healthy subjects - Carotti, M.; Salaffi, F.; Morbiducci, J.; Ciapetti, A.; Bartolucci, L.; Gasparini, S.; Ferraccioli, G.; Giuseppetti, G.M.; Grassi, W. (European journal of radiology, 2012)
To evaluate the presence of blood flow by colour Doppler ultrasonography (CDUS) in the wrist and finger joints of rheumatoid arthritis (RA) patients and healthy subjects and to define a cut-off value of CDUS resistive index (RI). Forty-three patients with RA and 43 healthy controls were examined by CDUS. The wrists, second and third metacarpophalangeal (MCP) and proximal interphalangeal (PIP) joints were evaluated in each patient and healthy subject. Spectral Doppler analysis was performed in order to characterize the type of flow and a mean RI was measured to define a cut-off level. The area under receiver operating characteristic curve was used to evaluate the screening method's performance. Flow was detected in 219 of the 430 total joints (50.9%) of RA patients (111 in the wrists, 49 in the MCP and 30 in the PIP joints). Healthy subjects had a quantifiable flow in 45 of the 430 joints (10.5%) and, in particular, 39 (86.4%) in the wrist, 5 (11.14%) in the MCP and 1 (2.2%) in the PIP joints. The intra- and inter-reader agreements for the detection of Doppler signal were very good (kappa 0.82 and 0.89, respectively). Mean RI values were 0.72±0.06 in RA patients and 0.86±0.06 in healthy subjects (p<0.01). At cut-off point of RI<0.79 the sensitivity was 89.6% and the specificity was 78.8% (positive likelihood ratio 4.22). DUS is a useful tool for the detection of abnormal blood flow in inflammatory joints of RA patients.